Respuesta :
[tex]\left( \cfrac{x^3}{y^5} \right)^2=\cfrac{(x^3)^2}{(y^5)^2}=\cfrac{x^{3*2}}{y^{5*2}}=\cfrac{x^{6}}{y^{10}}[/tex]
Answer:
Option 3 - x to the 6th power over y to the 10th power
Step-by-step explanation:
Given : Expression x to the 3rd power over y to the 5th power all raised to the 2nd power.
To find : Choose the correct simplification of the expression?
Solution :
Writing the expression in value form,
x to the 3rd power = [tex]x^3[/tex]
y to the 5th power= [tex]y^5[/tex]
x to the 3rd power over y to the 5th power all raised to the 2nd power =
[tex](\frac{x^3}{y^5})^2[/tex]
Now applying identity,
[tex](\frac{x}{y})^a=\frac{x^a}{y^a}[/tex]
[tex]=(\frac{x^3}{y^5})^2[/tex]
[tex]=\frac{(x^3)^2}{(y^5)^2}[/tex]
Using identity, [tex](x^a)^b=x^{a.b}[/tex]
[tex]=\frac{x^{3.2}}{y^{5.2}}[/tex]
[tex]=\frac{x^{6}}{y^{10}}[/tex]
In word form, x to the 6th power over y to the 10th power.
Therefore, Option 3 is correct.